Reduction of Income Tax Rate and Compliance of MSME Taxpayers: a Study in the Perspective of Islamic Economic Philosophy - Isnaeni, Ahmad; Liya Ermawati; Fitri, Ainul (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to evaluate the impact of reduced income tax rates on taxpayer compliance Micro, Small, and medium enterprises (SMEs) in the perspective of Islamic economic philosophy. The research method used is a mixed approach (mixed methods). Quantitative Data were obtained from reports on the number of taxpayers who reported tax returns to the Bengkulu–Lampung DGT Regional Office in 2017-2020 and questionnaires, while qualitative data were obtained through interviews with MSME actors and Islamic economics experts. The results showed that the decrease in income tax rate has a positive effect on the compliance of MSME taxpayers. In addition, tax awareness also has a positive and significant effect on MSME taxpayer compliance. Taxpayers who have an understanding and commitment to principles in Islamic economics, such as zakat and social responsibility, tend to be more compliant in reporting and paying taxes.